INCU Analyzer for Infant Incubator Based on Android Application Using Bluetooth Communication to Improve Calibration Monitoring - Vijay Anant Athavale; Abhilash Pati; A K M Bellal Hossain; Sari Luthfiyah; Triwiyanto Triwiyanto (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Worldwide, over 4 million babies die within a month of birth each year. Of these, 3.9 million are in developing countries. A proportion approximately 25% of these deaths are due to complications of premature birth, most commonly inadequate thermoregulation, water loss, and neonatal jaundice. An infant incubator provides stable temperature, relative humidity, and airflow values. A periodical calibration should be applied on infant incubator to monitor the functionality. The study aims to develop a calibration device that measures temperature, humidity, airflow, and noise in the baby incubator based on an Android application with Bluetooth communication to improve the calibration monitoring process. This is to achieve a better performance of the conventional INCU analyzer. The contribution of this research is that the values of the temperature, humidity, airflow, and noise can be displayed on both devices, the INCU analyzer machine, and mobile phone; thus, the user can monitor the measurement activities wirelessly. Furthermore, the statistical calculation for all measurements can be saved on a mobile phone device. The main design consists of temperature sensor LM35, humidity sensor DHT22, airflow sensor MPX5010DP, an analog signal conditioning circuit, an Arduino Mega microcontroller, Bluetooth module HC05, and Android mobile phone. The resulting design was compared to the standard or calibrator INCU analyzer machine (Fluke Biomedical INCU II). This study found that the smallest error is -1.72%°C, -0.106 % RH, -1.727% dB, and <0.1% m/s for temperature, humidity, noise, and airflow parameters, respectively. After the evaluation process, this device can be used as an INCU analyzer to calibrate the infant incubator.